L’expérimentation et la lutte. Le cours Sur la peinture de Deleuze - D’Aurizio, Claudio (Scenari, 2024)
This paper aims to propose some insights starting from the text of the lectures On painting given by Deleuze in the spring of 1981. The recent publication of these lectures allows to observe some issues that closely concern Deleuze’s thought, especially regarding his concepts of ‘creation’ and ‘resistance’. The paper intends to show the way in which, through a reflection on painting, Deleuze develops a method of reading and problematising that inextricably unites the theme of struggle with the theme of experimentation. This intertwining could be seen as one of the theoretical nucleuses that gives birth to the connection between creation and resistance, both in art and philosophy, which will be more profoundly explored in his later philosophical production.